Sustainable Lifeways: Cultural Persistence in an Ever-Changing Environment - Ramsey, Monica (Ethnobiology Letters, 2013)
Book review of Sustainable Lifeways: Cultural Persistence in an Ever-Changing Environment. Naomi F. Miller, Katherine M. Moore, Kathleen Ryan, editors. 2011. University of Pennsylvania Press, Philadelphia. Pp. 352, 73 illustrations. 65.00 (cloth). ISBN 9787934536193.